Reducing Saturation‐Current Density to Realize High‐Efficiency Low‐Bandgap Mixed Tin–Lead Halide Perovskite Solar Cells. Issue 3 (27th November 2018) - Li, Chongwen; Song, Zhaoning; Zhao, Dewei; Xiao, Chuanxiao; Subedi, Biwas; Shrestha, Niraj; Junda, Maxwell M.; Wang, Changlei; Jiang, Chun‐Sheng; Al‐Jassim, Mowafak; Ellingson, Randy J.; Podraza, Nikolas J.; et al.
Abstract: The unsatisfactory performance of low‐bandgap mixed tin (Sn)–lead (Pb) halide perovskite subcells has been one of the major obstacles hindering the progress of the power conversion efficiencies (PCEs) of all‐perovskite tandem solar cells. By analyzing dark‐current density and distribution, it is identified that charge recombination at grain boundaries is a key factor limiting the performance of low‐bandgap mixed Sn–Pb halide perovskite subcells. It is further found that bromine (Br) incorporation can effectively passivate grain boundaries and lower the dark current density by two–three orders of magnitude. By optimizing the Br concentration, low‐bandgap (1.272 eV) mixed Sn–Pb halide perovskite solar cells are fabricated with open‐circuit voltage deficits as low as 0.384 V and fill factors as high as 75%. The best‐performing device demonstrates a PCE of >19%. The results suggest an important direction for improving the performance of low‐bandgap mixed Sn–Pb halide perovskite solar cells. Abstract : Charge recombination at grain boundaries is a key factor limiting the performance of low‐bandgap mixed tin–lead halide perovskite solar cells. It is found that bromine incorporation can passivate grain boundaries and lower the dark current density by two to three orders of magnitude. The champion cell shows an open‐circuit voltage deficit of 0.384 V and power conversion efficiency exceeding 19%.